2018
DOI: 10.4103/jfcm.jfcm_117_17
|View full text |Cite
|
Sign up to set email alerts
|

Stress, anxiety, depression, and sexual dysfunction among postmenopausal women in Shiraz, Iran, 2015

Abstract: BACKGROUND:Menopause is associated with decreased sexual activity and a feeling of decreased attractiveness and sexual potency. This study tested the hypothesis that sexual health in postmenopausal women is not the same as nonmenopausal women with regard to symptoms of stress, anxiety, and depression.MATERIALS AND METHODS:This cross-sectional study was conducted in 12 health centers in Shiraz between April and September 2015; 310 postmenopausal women included by convenient sampling. Data were collected through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Additionally, some studies indicated that postmenopausal women experience aging, altered mental image of their appearance, and feelings of femininity end, disability, disappointment, depression, and anxiety which can influence their sexual function 72. In line with the results of some control studies,17213953 Borissova et al73 reported that decreased libido in postmenopausal women may be related to some psychological factors like depression. Danaci et al74 indicated that anxiety and depression have a profound effect on sexual relationships.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Additionally, some studies indicated that postmenopausal women experience aging, altered mental image of their appearance, and feelings of femininity end, disability, disappointment, depression, and anxiety which can influence their sexual function 72. In line with the results of some control studies,17213953 Borissova et al73 reported that decreased libido in postmenopausal women may be related to some psychological factors like depression. Danaci et al74 indicated that anxiety and depression have a profound effect on sexual relationships.…”
Section: Discussionsupporting
confidence: 59%
“…In Iran, Kabudi,20 in his research on the knowledge about menopause and sexual function of women over 35 years old in Kermanshah, reported that sexual dysfunction responses in two phases of sexuality and erection in 141 menopausal women is 70%. However, Yazdanpanahi et al21 reported the prevalence of sexual dysfunction during menopause as much as 88.7%. In another report in 2002 from the USA, this rate was 30% 22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some menopause complications include menopausal flushing, insomnia, changes in sexual function, mood disorders, late cardiovascular complications, and osteoporosis [ 6 ]. Sexual dysfunction is also a common complaint in menopause [ 7 ]. Sexual function means engaging in sexual intercourse as she wishes, including desire (libido), arousal (excitement), orgasm and resolution with consent and without pain.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) showed the relationship between a mental state-like depression, anxiety, and stress with sexual dysfunction These findings draw the much-needed attention to the need to investigate the menopausal symptoms, the psychological problems of couples, and their lack of sexual knowledge in order to give them the necessary counseling and instruction. [ 1 ]…”
mentioning
confidence: 99%